2016
DOI: 10.1016/j.jastp.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Inter-hourly variability of Total Electron Content during the quiet condition over Nigeria, within the Equatorial Ionization Anomaly region

Abstract: To cite this version:T.T. Ayorinde, A. B Rabiu, Christine Amory-Mazaudier. Inter-hourly variability of total electron content during the quiet condition over Nigeria, within the equatorial ionization anomaly region. AbstractThe inter-hourly variability (IHV) of the Total Electron Content (TEC) over Nigeria during the quiet days (Ap<4) of the year 2013 was examined using ground-based GPS receivers installed at seven (7) different locations across Nigeria by the Nigerian Global Navigation Satellite Systems (GNSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Studies on diurnal variation in TEC reveal useful information about the physical processes responsible for the ionospheric behaviour and TEC is fast becoming an impor-tant parameter for both geophysical and engineering applications (Pandey et al, 2001;Mukherjee et al, 2010). In Nigeria, Bolaji et al (2012) reported that during low solar activity the TEC over Ilorin, a station close to the trough of the EIA, exhibits consistent minimum diurnal variation during presunrise hours between 05:00 and 06:00 LT, rises steeply during the sunrise period (07:00-09:00 LT), and subsequently rises very slowly from 10:00 LT to the peak during the daytime, mostly around 12:00-16:00 LT. Bagiya et al (2009) had earlier reported similar diurnal variation patterns during low solar activity periods near the crest region of the EIA in India and confirmed that the diurnal characteristics of TEC depend on season, solar activity, geomagnetic activity, and latitude.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…Studies on diurnal variation in TEC reveal useful information about the physical processes responsible for the ionospheric behaviour and TEC is fast becoming an impor-tant parameter for both geophysical and engineering applications (Pandey et al, 2001;Mukherjee et al, 2010). In Nigeria, Bolaji et al (2012) reported that during low solar activity the TEC over Ilorin, a station close to the trough of the EIA, exhibits consistent minimum diurnal variation during presunrise hours between 05:00 and 06:00 LT, rises steeply during the sunrise period (07:00-09:00 LT), and subsequently rises very slowly from 10:00 LT to the peak during the daytime, mostly around 12:00-16:00 LT. Bagiya et al (2009) had earlier reported similar diurnal variation patterns during low solar activity periods near the crest region of the EIA in India and confirmed that the diurnal characteristics of TEC depend on season, solar activity, geomagnetic activity, and latitude.…”
Section: Introductionsupporting
confidence: 71%
“…The Ionospheric GPS TEC was obtained from the ground-based GPS receiver stations of NIGNET equipment being operated by the Office of the Surveyor General of the Federation (OSGoF) of Nigeria for the year 2012. Description of the NIGNET network and the managing agency is given in Rabiu et al (2014) and Ayorinde et al (2016).…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
See 3 more Smart Citations